Climate action for (my) children - Helena Fornwagner; Oliver P. Hauser (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
Sustaining large-scale public goods, such as the environment, requires individuals to take action; however, motivating voluntary climate action (VCA) is difficult because decision-makers today do not stand to benefit from their investments. Here, we propose that parents invest more in VCA if their link to future generations-through their offspring-is made salient. In a novel lab-in-the-field experiment, we vary whether parents are observed during a VCA decision (i.e., investing in planting real-world trees) by their own child. In addition to a no-observer control, we run additional control conditions with an unrelated adult or an unrelated child observing the parent decision-maker. As predicted, VCA varies across conditions, with larger treatment effects occurring when a parent's own child is the observer. In subgroup analyses, larger treatment effects occur among more educated parents. As a result of this study, VCA across conditions led to 14,000 trees being planted, offsetting approximately 8% of participants' annual CO2 emissions for around four generations.
Keywords: C99; Q51; Q54; H49; D19; 330; voluntary climate action; intergenerational cooperation; parents; children; observability; lab-in-the-field experiment